Workload Analysis of Production Workers at PT Mitra Maharta: Applying the NASA-TLX and Full-Time Equivalent Methods - Maulana Malik Agungdiningrat; Rusindiyanto Rusindiyanto; Mega Cattleya Prameswari Annissaa Islami (Yayasan Riset dan Pengembangan Intelektual, 2024)
Combine Harvester is one of the products of PT Mitra Maharta that requires high work demands and accuracy in the production process. Workers in the production division tend to cause uneven workloads due to intensive labor demands and the obligation to work with high accuracy. Therefore, measurements of the workloads experienced by workers are needed. The NASA-TLX and FTE (Full Time Equivalent) methods were used to measure the workloads of 14 production workers. Some workers have an average WWL value from the range of 64 - 84.33 with the categories “High” to “Very High” in the NASA-TLX calculation, while in the FTE method calculation, they have an FTE index value from the range of 0.79 - 1.32 with the categories “Underload”, “Normal”, and “Overload”. Recommendations from this study include task restructuring and reallocation of human resources, additional manpower, as well as policies such as adequate rest time and training to improve worker efficiency.